Spatial Ambient Remapping - Rocha, Henry Furquim; Braga, Gustavo Beltrão; Braga, Pedro Luiz da Costa; Eller, Vitor Grando; Soares, Luciano Pereira (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais do XXIV Simpósio de Realidade Virtual e Aumentada, 2022)
A challenge in Spatial Computing considering markerless Augmented Reality is to anchor virtual objects relative to a physical space so that objects positions are stable across different tracking and augmented reality devices. This process must be stable in conditions that distinct devices can identify a real space by different strategies and that later the virtual objects appear in the same absolute location. This will also enable user to remotely edit an augmented environment using as reference a real environment. The goal of this research project is a platform that allows to remotely edit an augmented reality scenario referenced in a space previously digitized by a point cloud scan. Editing augmented environments allows users to add new virtual objects in a previously scanned physical space context remotely, enabling a new experience for the user who is interacting in augmented reality locally. A functional prototype of a desktop editor and a mobile application was developed that allows the visualization of environments remotely edited for Augmented Reality. Tests and simulations showed the feasibility of the proposed solution.